Contesting Caucasus: Comparative analysis of Türkiye and Russia’s Karabakh policies - Ahmet Turan (Faculty of Social and Political Science, Universitas Airlangga, 2026)
The Karabakh conflict has remained on the agenda of the international community for 30 years. During the Second Karabakh War, Türkiye supported Azerbaijan by all means, while Russia sided with Armenia. This reignited the historic rivalry between them. Azerbaijan’s victory in the war also positioned Ankara as the superior power in the Türkiye Russia rivalry in the Caucasus. The primary aim of this study is to measure the material power capacity of the two countries using objective criteria and identify the factors that provide Türkiye with an advantage in this competition. This quantitative study systematically compares the material power capacities of Türkiye and Russia using measurable and internationally recognized indicators. The findings suggest that the elements enhancing Türkiye’s regional influence are not limited to military capacity alone, and that diplomatic and economic factors also play a decisive role. In this context, this study concludes that the Turkish-Russian rivalry during the Second Karabakh War provides an example of how intermediary variables such as technological innovation, political commitment, and strategic interpretation can influence the balance of influence, even when structural indicators indicate different hierarchies.